Phospholipase D-neutralization in serodiagnosis of Arcanobacterium haemolyticum and Corynebacterium pseudotuberculosis infections - Skalka, B; Literák, I; Chalupa, P; Votava, M (Zentralblatt fur Bakteriologie, 1998)
Phospholipase D (PLD) neutralization was used to examine sera of humans (n = 40) with a spontaneous infection by Arcanobacterium haemolyticum, sheep and goats (n = 76 and 79 respectively) with a spontaneous infection by Corynebacterium pseudotuberculosis, mice (n = 26) experimentally immunized with PLD from A. haemolyticum (PLD-A) and mice (n = 28) experimentally immunized with PLD from C. pseudotuberculosis (PLD-C). PLD-A and PLD-C were also used as neutralizing antigens. A positive result of neutralization was due to an inhibition of the haemolytic synergism with the equi factor from Rhodococcus equi. The titres of sera neutralizing the homologous PLD were always significantly higher than those neutralizing the heterologous PLD. The proportion of sera that were able to neutralize the homologous PLD in sheep, goats and mice immunized with PLD-A significantly exceeded the proportion of sera that neutralized the heterologous PLD. The antigenic properties of PLD-A and PLD-C were similar but not identical.
Keywords: protilátky bakteriální; Animals; Goats; Neutralization Tests; Phospholipase D; Corynebacterium Infections; ovce; lidé; Corynebacterium pseudotuberculosis; Mice; fosfolipasa D; myši; nemoci koz; Antibodies, Bacterial; Actinomycetales; kozy; nemoci ovcí; sérologické testy; Sheep; Goat Diseases; neutralizační testy; Serologic Tests; infekce bakteriemi řádu Actinomycetales; zvířata; korynebakteriální infekce; Actinomycetales Infections; Sheep Diseases; Humans